Possible Role of E-Cadherin, CD86 and L-Selectin in Antiapoptotic Mechanisms of Ulcerative Colitis - Ja'afar, Areeg Hamad; Abdul-Muhaymen, Nidhal; Al-Khurri, Luay Edward (Al-Nahrain Journal of Science, 2013)
The current study was designed to determine the pattern of E-cadherin, CD86 and L-selectin expression in different histopathological grades of activity of ulcerative colitis (UC), and to determine the degree of apoptosis in patients with UC and whether this apoptotic death could be correlated with cellular expression of E-cadherin, CD86 and L-selectin in different histopathological grades of activity of UC.Forty five paraffin-embedded UC samples and 10 resection margins of colectomy specimens for diseases other than UC (control group) were enrolled in this study. The age range of the patients was 9-70 years and 18 were females while 27 were males. Hematoxylin and Eosin stained sections were used to define the disease activity.Adequate, 4 µm thick sections of both UC and resection margins samples were prepared and used to detect E-cadherin, CD86 and L-selectin expression employing immunohistochemical analysis. Evaluation of apoptosis in mucosa with UC was performed using the TUNEL assay.Based on current outcome, by immunohistochemical analysis, there was a significant down regulation in E-cadherin expression and over expression of CD86 in the inflamed mucosa compared to control group and the differences were statistically significant in both compared to control group (p < 0.05).The expression of L-selectin was relatively higher in the inflamed mucosa compared to controls but the frequencies and percentages of L-selectin expression between patients and controls were statistically not significant (p > 0.05).Using the TUNEL assays, thirty cases were investigated for evaluation of apoptosis. The results showed that the number of TUNEL positive cells was not significantly different from that in the control group and the frequencies and percentages of apoptosis between patients and controls in both lymphocytes and epithelial cells were statistically not significant (p > 0.05).None of the four investigated parameters including E-cadherin, CD86, L-selectin and apoptosis demonstrated any significant correlations of their expressions with the grade of inflammation (p > 0.05).